A PROBLEMATIC APPROACH TO THE ORGANIZATION OF INDEPENDENT WORK AS A MEANS OF IMPROVING THE QUALITY OF KNOWLEDGE OF STUDENTS OF THE PEDAGOGICAL UNIVERSITY (Pedagogy of Higher and Secondary Education, 2010)
The article deals with the problem concerning self-directed independent activities at a teacher training higher educational establishment on the basis of a task approach as the means of improvement student s knowledge quality.
Keywords: task approach; self-directed independent activities of students; motivation of learning; cognitive activities; student’s knowledge quality